(untitled) (The Journal of Psychology and Sociology, 2024)
This article review explores the multifaceted phenomenon of cyberbullying within the contemporary digital landscape. The research aims to provide a comprehensive understanding of cyberbullying by synthesizing key findings from a diverse range of scholarly works. The purpose of this scientific inquiry is to unravel the complex dimensions of cyberbullying, emphasizing its diverse forms, prevalence across demographics, and the profound psychological impact on victims. The research methodology involves a systematic literature review, wherein relevant articles are identified, selected, and critically evaluated. An extensive and systematic search for relevant articles from peer-reviewed journals prioritized publications from the last decade to analyze recent research findings on cyberbullying. The analysis provided a better understanding of the complexities associated with cyberbullying in today’s digital age. The scientific and practical significance of this work lies in its contribution to the ongoing discourse on cyberbullying. The synthesis of research findings offers a nuanced perspective on the international experience of cyberbullying, recognizing the global prevalence while acknowledging cultural variations. The value of this research lies in its contribution to advancing knowledge on cyberbullying. By synthesizing diverse perspectives, the article review offers a holistic understanding of the phenomenon, guiding future research initiatives and safety policy development. Key words: cyberbullying, digital aggression, internet safety, psychological well-being.